Intraspecific variation in the Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) susceptibility to insecticides Variabilidade intraespecífica na suscetibilidade de Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) a inseticidas - Restelatto S.S.* (2021)
© 2021, Universidade Federal De Goias (UFG). All rights reserved.The looper caterpillar Chrysodeixis includens (Walker) is considered the main defoliating pest in soybean crops, which contributes to yield losses. Delaying its resistance to insecticides is a major challenge in its management. This study aimed to characterize the susceptibility of C. includens to flubendiamide, cyantraniliprole, spinetoram and methomyl, as well as to establish a diagnostic concentration for monitoring resistance. The insecticide was applied to the surface of the artificial diet. For the dose-response curve, concentrations that resulted in 5 to 99% mortality were used to estimate the lethal concentrations (LC50 and LC99) and resistance ratios (RR50 and RR99). The diagnostic concentrations were based on concentrations that provided 90 to 99% mortality in the susceptible reference population. For flubendiamide and methomyl, the decrease in the susceptibility resulted in estimated RR50 of 6.2 to 24.2 and 4.4 to 19.6 times, respectively. For cyantraniliprole and spinetoram, there was little difference in susceptibility among the populations, with RR99 lower than 6.1 times. Differences in the susceptibility of C. includens were evident from concentrations of 0.5053, 5.053, 0.1579 and 28.42 μg cm-2, respectively for flubendiamide, cyantraniliprole, spinetoram and methomyl.